Equivalence Partitions Method on Black Box Testing of Motor Service Information Systems at CM Jaya Motor Kudus Web-Based with SMS Gateway - Noor Latifah; Diana Laily Fithri; Fajar Nugraha; Yudie Irawan; Zulfa Himmatul Ulya (Journal of Information Technology Ampera, 2022)
CM Jaya Motor is located on Jl. Sunan Kudus No.100 Demaan Kudus is a service business in the field of motorcycle maintenance, especially the Honda motorcycle brand, to increase the satisfaction of the services provided to customers, a motorcycle service information system was built at CM Jaya Motor. The motorbike service information system at CM Jaya Motor Kudus aims to make it easier for customers. The motor service information system at CM Jaya Motor Kudus before being implemented requires testing the system or software first, this is done to be able to find deficiencies and errors that still occur in the system. Tests in this study used the black box method with the evaluation partition technique. Black box testing is carried out without detailed knowledge of the internal structure of the system or component being tested. Obtaining Equivalence Partitions Test Case Design from the evaluation of the Equivalence class which shows the state of the input process, a collection of valid and invalid conditions. The test results show that the quality of the Motor Service Information System at Web-Based CM Jaya Motor Kudus with SMS Gateway still needs to be improved.